A self-matching, ultra-fast film forming and washable removal bio-crosslinked hydrogel films for perishable fruits. (1st September 2021) - Deng, Yongfu; Huang, Guohuan; Zhao, Wenxin; Li, Xiaoxing; Zhang, Yuancheng; Wei, Fuxiang; Lin, Zhenhao; Lin, Baofeng
Abstract: Spoilage of food has aggravated the issue of food shortage worldwide. Here, we report a strategy for ultrafast hydrogel film forming within 10 s on fruit surfaces with good self-matching, washable removal and preservative property. This carboxymethyl chitosan (CMCS)/tannic acid (TA) hydrogel film (CTHF) is fabricated by bio-material of CMCS and TA via in-situ rapidly crosslinking with high-density hydrogen bonds. Simply blending TA and CMCS solution at room temperature can form CTHF with different roughness (Ra: ranges from 123 to 1.55 nm) on different fruit surfaces, so as to perfectly match the hydrogel protective layer of pericarp. The CTHF slows down fruit decay by its outstanding antioxidant and antibacterial activity. It is soluble and easily removed (within 3–5 min) by washing without environmental pollution and food safety issues. As natural polymer, CTHF shows high promise as sustainable substitutes for conventional plastics packing because of its non-toxic, edible, biodegradable, and environmentally friendly. Graphical abstract: Unlabelled Image Highlights: A novel strategy for ultrafast film forming within 10 s on fruit surfaces By in-situ rapid crosslinking, the film can be formed on smooth or rough fruit. Smart bio-packing with self-matching, effectively prolong the shelf life of fruit. The film is nontoxic, washable removal, and biodegradable.